Company Resilience and Competitiveness Sourced from Dynamic Managerial Capability with Transformation Digital Moderation - Eduard Alfian Syamsya Sijabat (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2025)
The competitiveness and resilience of service companies are related to dynamic managerial capabilities. Dynamic managerial capabilities that are well managed by the company will produce competitiveness and resilience. This study aims to examine the competitiveness and resilience of companies that rely on the management of dynamic managerial capabilities with the moderation of digital transformation. The object of the research is shipping agency companies in Indonesia that operate in the 5 main ports in Indonesia. Data collection was carried out online by distributing questionnaires and analysed statistically using WARPls. The results showed that dynamic managerial capabilities had a significant effect on resilience and competitiveness. The digital transformation adopted by the company shows the strengthening of dynamic managerial capabilities in influencing the company's competitiveness. Different results showed that digital transformation weakens the dynamic managerial capabilities in influencing the company's resilience. The results of this study contribute implications in enriching the empirical testing of the theory of competitive advantage based on the resource-based view (RBV). The results of this study contribute practically to the shipping agency service industry in Indonesia, which shows that the digital transformation adopted by the company will strengthen the dynamic managerial capabilities towards competitiveness while its weaken the company resilience.